An Integrated Microfluidic Probe for Mass Spectrometry Imaging of Biological Samples. Issue 50 (9th October 2020) - Li, Xiangtang; Yin, Ruichuan; Hu, Hang; Li, Yingju; Sun, Xiaofei; Dey, Sudhansu K.; Laskin, Julia
Abstract: Ambient ionization based on liquid extraction is widely used in mass spectrometry imaging (MSI) of molecules in biological samples. The development of nanospray desorption electrospray ionization (nano‐DESI) has enabled the robust imaging of tissue sections with high spatial resolution. However, the fabrication of the nano‐DESI probe is challenging, which limits its dissemination to the broader scientific community. Herein, we describe the design and performance of an integrated microfluidic probe (iMFP) for nano‐DESI MSI. The glass iMFP, fabricated using photolithography, wet etching, and polishing, shows comparable performance to the capillary‐based nano‐DESI MSI in terms of stability and sensitivity; a spatial resolution of better than 25 μm was obtained in these first proof‐of‐principle experiments. The iMFP is easy to operate and align in front of a mass spectrometer, which will facilitate broader use of liquid‐extraction‐based MSI in biological research, drug discovery, and clinical studies. Abstract : An integrated microfluidic probe (iMFP) is designed and produced to enable the broader use of liquid‐extraction‐based mass spectrometry imaging (MSI). It is easy to align and its stability and sensitivity are comparable to capillary‐based nanospray desorption electrospray ionization (nano‐DESI) MSI. The iMFP was used to image phospholipid distribution in mouse uterine tissue with a spatial resolution of better than 25 μm.